Loneliness, Spirituality, and Health-Related Quality of Life in Hispanic English-Speaking Cancer Caregivers: A Qualitative Approach - King, Jennifer J. (Journal of religion and health, 2024)
Hispanic caregivers experiencing higher caregiving burden than their non-Hispanic cohorts, due in part to contextual factors, such as barriers to accessing health care, challenging employment environments, low education and income, immigration issues, and minority stress. Spirituality may serve as a coping strategy for Hispanic caregivers that influences health-related quality of life (HRQoL), possibly by modifying loneliness associated with caregiving. We explored these concepts using semi-structured interviews (N = 10 Hispanic caregivers). Participants shared perceptions of loneliness, spirituality, and how these factors related to HRQoL. Five themes emerged: caregiver experience, coping strategies, loneliness, religion and spirituality to gain strength. Findings suggested that spirituality and religion improved HRQoL partially by reducing loneliness. Future programs to improve HRQoL in Hispanic English-speaking cancer caregivers should address spirituality.